Conceptualising the Importance of Metaverse in Education: A Bibliometric Analysis - Verma , Anuj; Patil, Prachita; Paliwal, Jai Prakash M; Bakhare, Ruhi; Pillai, Rajani; Singh, Mahesh (Journal of Ecohumanism, 2024)
The unification of metaverse in education asserts a transformative alteration, redefining the conventional learning pedagogy. This study explores the swelling integration of artificial intelligence and immersive technologies in education system. As the learners and educators increasingly engage themselves in the digital medium of communication, the metaverse offers a wider scope for inclusive and experiential learning. The metaverse’s ability of transcending topographical boundaries provides an all-encompassing platform for comprehensive education, nurturing cross cultural knowledge with varied perspectives. While the metaverse presents unparalleled prospects for innovation, it also raises considerations pertaining to accessibility and privacy. Through this study the authors have analysed the contemporary topics of metaverse in education by blending multi perspective approach using bibliometric analysis with diverse and disciplinary features of the metaverse and its metamorphic outcome. Ultimately, this study accentuates the budding landscape of education with metaverse as a prevailing tool embracing engagement and all-inclusive learning experience.